Orally active epoxyeicosatrienoic acid analog does not exhibit antihypertensive and reno- or cardioprotective actions in two-kidney, one-clip Goldblatt hypertensive rats - Alánová, Petra; Husková, Zuzana; Kopkan, Libor; Sporková, Alexandra; Jíchová, Šárka; Neckář, Jan; Imig, John D; Klevstig, Martina; Kolář, František; Rami Reddy, N; Falck, John R; Sadowski, Janusz; et al. (Vascular pharmacology, 2015)
This study examined the effects of a novel orally active 14,15-epoxyeicosatrienoic acid analog (EET-A) on blood pressure (BP) and myocardial infarct size (IS) in two-kidney, one-clip (2K1C) Goldblatt hypertensive rats during sustained phase of hypertension. Between days 31 and 35 after clip placement the rats were treated with EET-A and BP was monitored by radiotelemetry; sham-operated normotensive rats were used as controls. Tissue concentrations of epoxyeicosatrienoic acids served as a marker of production of epoxygenase metabolites. The rats were subjected to acute myocardial ischemia/reperfusion (I/R) injury and IS was determined. We found that EET-A treatment did not lower BP in 2K1C rats and did not alter availability of biologically active epoxygenase metabolites in 2K1C or in sham-operated rats. The myocardial IS was significantly smaller in untreated 2K1C rats as compared with normotensive controls and EET-A reduced it in controls but not in 2K1C rats. Our findings suggest that during the phase of sustained hypertension 2K1C Goldblatt hypertensive rats exhibit increased cardiac tolerance to I/R injury as compared with normotensive controls, and that in this animal model of human renovascular hypertension short-term treatment with EET-A does not induce any antihypertensive and cardioprotective actions.
Keywords: telemetrie; Animals; Kidney; Proto-Oncogene Proteins c-akt; Myocardial Reperfusion Injury; Hydroxyeicosatetraenoic Acids; Time Factors; časové faktory; kyseliny hydroxyeikosatetraenové; renin-angiotensin systém; Blood Pressure Monitoring, Ambulatory; Renin-Angiotensin System; renovaskulární hypertenze; signální transdukce; reperfuzní poškození myokardu; Signal Transduction; krevní tlak; Rats, Sprague-Dawley; protoonkogenní proteiny c-akt; kyselina 8,11,14-eikosatrienová; Male; modely nemocí na zvířatech; potkani Sprague-Dawley; Telemetry; aplikace orální; Hypertension, Renovascular; 8,11,14-Eicosatrienoic Acid; ambulantní monitorování krevního tlaku; Disease Models, Animal; Myocardial Infarction; kinasa 3 glykogensynthasy; Administration, Oral; zvířata; mužské pohlaví; Glycogen Synthase Kinase 3; Blood Pressure; ledviny; myokard; Myocardium; infarkt myokardu